Development of a Solar-Powered Portable Watering Device Using an Ergonomic Approach to Improve User Comfort and Reduce Costs - Firman Ardiansyah Ekoanindiyo; Antoni Yohanes; Eri Zuliarso; Eka Ardhianto; Retnowati; Kristiawan Nugroho (Logic : Jurnal Rancang Bangun dan Teknologi, 2026)
Farmers in many rural areas still depend on gasoline-powered irrigation pumps, which create recurring fuel costs, noise, emissions, and awkward operating postures. Existing studies have widely discussed solar-powered irrigation systems and automatic watering technologies; however, limited attention has been given to a portable prototype that simultaneously integrates renewable energy use and ergonomic design for small-field operation. This study developed a solar-powered portable watering device and evaluated its technical and ergonomic performance in the Sido Maju Farmer Group, Kendal Regency, Indonesia. The prototype used a 350 Wp photovoltaic panel to supply a DC pump mounted on a wheeled frame. The ergonomic configuration was determined from farmers’ anthropometric dimensions, including a handle height of about 95 cm, frame height of 110–120 cm, and wheel diameter of 30 cm. The study applied a prototype-development approach followed by field trials, direct observation, and user questionnaires. Quantitative indicators included fuel-cost reduction, watering duration, mobility, and comfort scores, while qualitative data were obtained from farmer interviews. The results show that the proposed device reduced direct fuel expenditure from approximately Rp1,200,000 per planting season to Rp0, equivalent to about Rp4,800,000 in annual savings. The ergonomic evaluation also showed high user acceptance, with average scores of 4.6/5 for ergonomics and working posture, 4.7/5 for environmental working conditions, and 4.4/5 for efficiency and ease of use. These findings indicate that the device offers a practical contribution by combining solar energy utilization, portability, and ergonomic improvement in one agricultural watering system. The prototype can therefore support lower operating costs, better user comfort, and more sustainable irrigation practices for small-scale farming.